Bioactivity and microbial content of Lippia multiflora leaves, a herbal tea from Ghana - Arthur, Hanson (Stellenbosch : University of Stellenbosch, 2009)
Thesis (Msc Food Sc (Food Science))--University of Stellenbosch, 2009.